Evaluating the performance of history teachers in light of the overall quality standards (Journal of the College of Basic Education, 2022)
Search aims to:1-Determine the comprehensive quality standards required for history teachers at the primary level. 2-Evaluation of the performance of history teachers in light of the criteria mentioned above. To achieve the objectives of the research, the researcher relied on the descriptive approach and a number of procedures that included the identification of the research community, which was limited to the history teachers in the primary schools of the General Directorate of Education Baghdad / Rusafa first, for the academic year (2016-2017), the number of (60) (24%) with a percentage of (40%) and (36) teachers with a percentage of (60%. The researcher used the questionnaire to collect his research data prepared by means of exploratory study, previous studies and literature related to the subject of the research, and to inform the researcher of a number of lists prepared by the specialists in the field of total quality, and after verifying its honesty by presenting them to the experts. The tool consists of (50) paragraphs divided into (8) main areas: (personal criteria, cultural standards, professional standards, scientific standards, ethical standards, intellectual standards, psychological and educational standards). to evaluate the teachers Date in the light . The researcher used a number of appropriate statistical methods (such as squares to test the validity of the paragraphs in the responses of the arbitrators, and Pearson correlation coefficient to extract the stability of the tool The study resulted in several results including1-Determine the comprehensive quality standards required for history teachers at the primary level .2-The level (average) ranked first among the five assessment levels included in the observation form, while the level (good) ranked third, while the (weak) ranked fourth, and the level that ranked last among the five levels is the level (very good In light of the results of the study, the researcher concluded that the performance of teachers of history in the primary stage in general was acceptable, which calls for more attention to the preparation and training of history teachers in the light of the overall quality standards, and the researcher made a number of recommendations and proposals. Opening words: performance calendar, history